2019
DOI: 10.1111/jomf.12592
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Religious Participation in Adolescence and Provision of Assistance to Older Mothers

Abstract: Objective: This investigation examined the association between intergenerational religious activities in adolescence and provision of assistance to older mothers up to 45 years later. Background: Guided by perspectives of the life course and intergenerational solidarity, this research tested whether children's early religious participation with mothers predicted the amount of assistance children later provided, whether mothers' disability and widowhood served as moderators of this relationship, and whether any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Religion is an important determinant of family solidarity. People who are religious tend to have stronger filial obligations than people who are not, and they also visit their parents more often and exchange more support with family members (Gans et al, 2009 ; Silverstein et al, 2019 ). As a result, one would expect that children and parents who are religious are more likely to live closer to each other than children and parents who are not religious.…”
Section: Introductionmentioning
confidence: 99%
“…Religion is an important determinant of family solidarity. People who are religious tend to have stronger filial obligations than people who are not, and they also visit their parents more often and exchange more support with family members (Gans et al, 2009 ; Silverstein et al, 2019 ). As a result, one would expect that children and parents who are religious are more likely to live closer to each other than children and parents who are not religious.…”
Section: Introductionmentioning
confidence: 99%
“…Intergenerational ties, in their behavioral, emotional, and normative manifestations, are strongly connected to religiosity (Myers, 2004; Pearce & Axinn, 1998; Stokes & Regnerus, 2009). Most religions emphasize the value of family life and provide arenas for intergenerational family activities, with long‐lasting impacts on intergenerational solidarity and filial responsibility (Silverstein et al, 2019). Previous research shows that by performing religious activities with their children, parents transmit values that emphasize respect and service to older generations, leading to strengthened intergenerational ties in adulthood (Clark et al, 1988; Hoge & Petrillo, 1978; Min et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the transition to established adulthood and accompanying dynamics of value reappraisal and entry into new family roles may alter former commitments to religious life (Barry et al, 2010; Hayward & Krause, 2013). Although studies have explored how religiosity changes through adulthood and across various life transitions (Desmond et al, 2010; Lee et al, 2017; Petts, 2009; Silverstein et al, 2019), little is known about how the development of religiosity in young adulthood relates to filial responsibility, specifically elder care norms, over time. The few existing studies on this topic are limited to cross‐sectional analyses that do not take into account the dynamic and multidimensional nature of religiosity across the demographically dense phase of young adult life (Gans et al, 2009; Goldberg‐Looney et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have examined the impact of religion on intergenerational relations in intact, nondivorced families, few researchers have explored similar questions regarding the impact of religion on intergenerational relations in stepfamilies. Research has found that adults who engaged in regular religious activities with their mothers in childhood provide more assistance to their mothers later in life (Silverstein, Zuo, Wang, & Bengtson, ), but the role of religion in intergenerational relationships within stepfamilies has not been explored. Therefore, in the present research, we use longitudinal dyadic data over 11 years to examine whether religious congruence between parents and adult children serves as such a mitigating factor.…”
mentioning
confidence: 99%